An Effective Way to Inspect the Cause of Fire at Factory and Warehouse Facilities Using the NFPA 921 Scientific Method - Kyung-Ho Kim; Ha-Sung Kong (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is to analyze the practices of fire cause inspection in the fire of factory and warehouse facilities, and suggest an effective inspection method applying the NFPA 921 scientific method. The findings of this study areas follows. First, in problem definition and data collection, if the combustion area is wide, and the process and operation method of machinery and facilities are complex, data omission can occur. Thus, this study suggests using the information system of fire-fighting organizations. Second, in data analysis and hypothesis development, as there is possibility of error in data analysis and insufficient legal objectivity in hypothesis development, this study suggests that fire inspector should secure video records along with statements of concerned persons and check manuals of machinery and facilities related with the fire. Finally, in hypothesis test and selection of the final hypothesis, this study suggests that, as the appraisal of the fire evidences can be insufficient, it is necessary for fire-fighting organization to make appraisal by itself using the equipments in the fire inspection and analysis room in the provincial and metropolitan fire departments and fire stations.